2013
DOI: 10.5005/jp-journals-10024-1373
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Pathogens and Respiratory Diseases— Evaluating Their Potential Association: A Clinical and Microbiological Study

Abstract: It is conceivable that oral interventions that improve oral health status may prove to lower the severity of lung infection in susceptible populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“… 27 , 34 , 35 Studies on nonsmoker COPD patients have also found an association of periodontal disease with COPD. 12 , 36 …”
Section: Discussionmentioning
confidence: 99%
“… 27 , 34 , 35 Studies on nonsmoker COPD patients have also found an association of periodontal disease with COPD. 12 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…Aspiration of oral pathogens into the lower respiratory tract was one of these hypotheses. 31 Periodontal disease-associated enzymes in saliva may also change respiratory environmental conditions, permitting mucosal colonization and infection by respiratory pathogens. 15 , 28 , 31 In addition, the association between poor oral health and respiratory disease was suggested to be mediated through systemic inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Periodontal disease-associated enzymes in saliva may also change respiratory environmental conditions, permitting mucosal colonization and infection by respiratory pathogens. 15 , 28 , 31 In addition, the association between poor oral health and respiratory disease was suggested to be mediated through systemic inflammatory responses. 9 , 32 Inflammatory cytokines, such as interleukin (IL)-6 or IL-8, from periodontal tissues may alter the respiratory epithelium to promote infection by respiratory pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The course of the pulmonary diseases can be affected by both infectious and inflammatory process, such as periodontitis (Azarpazhooh & Leake, 2006;Vadiraj, Nayak, Choudhary, Kudyar, & Spoorthi, 2013). The microorganisms present in the periodontal pocket, specially anaerobic bacteria, can be aspirated into the lower airway (Bansal, Khatri, & Taneja, 2013).…”
Section: Introductionmentioning
confidence: 99%